Phosphorus sorption, supply potential and availability in soils with contrasting parent material and soil chemical properties. (27th May 2015) - Daly, K.; Styles, D.; Lalor, S.; Wall, D. P.
Summary Soil phosphorus (P) management requires a more targeted and soil‐specific approach than is currently applied for agronomic recommendations and environmental evaluation. Phosphorus buffering capacities control the supply of P in the soil solution and were measured across Irish soils with contrasting parent material and chemical properties. Langmuir sorption buffer capacities (MBCs) and binding energies (b) were strongly correlated with soil pH and extractable aluminium (Al). A broken‐line regression fitted to the relationship between MBC and Al derived a change‐point value for Al above which MBC increased linearly. Soils above the change point were predominantly acidic to neutral with non‐calcareous parent material, with larger buffering capacities and binding energies than calcareous soils. Ratios of Mehlich3‐Al and P (Al:P) were used to relate buffering capacity to supply potential in non‐calcareous soils. Large ratios of Al:P were associated with poor P availability, characteristic of strongly P‐fixing soils. Threshold values of iron‐oxide paper strip P (FeO‐P) and Morgan's P revealed Al:P ratios where soils began to supply P in available form. The change‐point for Morgan's P fell within the current target index for P availability; however, the confidence interval was more compatible with previous agronomic P indices used in Ireland. Relationships between Morgan's P and measures of extractable P, M3‐P and Olsen P, deviated in calcareous soils at large soil P contents, indicative of P precipitation processes dominating in these soils. Identifying differences in soil P buffering capacity at the laboratory scale would improve agronomic and environmental assessment at field and catchment scales.